Attitude and awareness of general dental practitioners toward radiation hazards and safety - B S Aravind; E Tatu Joy; M Shashi Kiran; J Eugenia Sherubin; S Sajesh; P Redwin Dhas Manchil (Wolters Kluwer Medknow Publications, 2016)
Aim and Objective: The aim and objective is to evaluate the level of awareness and attitude about radiation hazards and safety practices among general dental practitioners in Trivandrum District, Kerala, India. Materials and Methods: A questionnaire-based cross-sectional study was conducted among 300 general dental practitioners in Trivandrum District, Kerala, India. Postanswering the questions, a handout regarding radiation safety and related preventive measures was distributed to encourage radiation understanding and protection. Statistical Analysis: Statistical analysis were done by assessing the results using Chi-square statistical test, t -test, and other software (Microsoft excel + SPSS 20.0 trail version). Results: Among 300 general practitioners (247 females and 53 males), 80.3% of the practitioners were found to have a separate section for radiographic examination in their clinics. Intraoral radiographic machines were found to be the most commonly (63.3%) used radiographic equipment while osteoprotegerin was the least (2%). Regarding the practitioner's safety measures, only 11.7% of them were following all the necessary steps while 6.7% clinicians were not using any safety measure in their clinic, and with respect to patient safety, only 9.7% of practitioners were following the protocol. Conclusion: The level of awareness of practitioners regarding radiation hazards and safety was found to be acceptable. However, implementation of their knowledge with respect to patient and personnel safety was found wanting. Insisting that they follow the protocols and take necessary safety measures by means of continuing medical education programs, pamphlets, articles, and workshops is strongly recommended.